Clinical Significance of Serum-Derived Exosomal LINC00917 in Patients With Non-Small Cell Lung Cancer - Xiong, Dani; Wang, Chuanlin; Yang, Zhaohui; Han, Fusen; Zhan, Huaibing (Frontiers in Genetics, 2021)
Background. In this study, we aimed to explore the diagnostic potential of serum-based exosomal long intergenic noncoding RNA 917 (LINC00917) in non-small cell lung cancer (NSCLC). Methods. Exosomes were extracted from NSCLC patients’ serum samples. Exosomal LINC00917 expression levels were compared, by qRT-PCR, between cancer patients and healthy controls, as well as sub-populations of cancer patients. The association between exosomal LINC00917 expression and NSCLC patients’ clinicopathologic factors were investigated, and receiver operating characteristic (ROC) curves were drawn. In addition, NSCLC patients’ overall survivals (OSs) was examined based on exosomal LINC00917 expression and further evaluated by the cox regression analysis. Results. Serum-derived exosomal LINC00917 was highly expressed in NSCLC patients, and further upregulated in stage III/IV cancer patients. Exosomal LINC00917 yielded modestly good under the curve (AUC) values. Upregulated exosomal LINC00917 expression was closely associated with cancer patients’ advanced stages and shorter OSs. Conclusion. Serum-derived exosomal LINC00917 may hold diagnostic potential for patients with non-small cell lung cancer